Efeitos das combinações de duas faixas de amplitude de conhecimento de performance na aquisição de uma habilidade motora - Madson Pereira Cruz (2016)
The aim of present study was to investigate the effects of the combination of two bandwidth Knowledge of Performance (KP) in the learning of a motor skill. The sample was composed by 30 elementary students, from 12 to 14 years old of both sexes, divided into three groups; a group that combined wide and narrow bandwidth KP (WNG); a group that combined narrow and wide bandwidth KP (NWG) and a control group CG, with 0% of bandwidth of KP. The question was investigated with the volleyball tennis serve, whose goal was to hit the bulls eye center of a target positioned on the floor of the opposite side of court. The study was composed of pretest, acquisition phase, intermediate test and retention test. During all tests the serves were recorded and the participants practiced 15 trials of the task end the score was written down. The acquisition phase consisted of 252 trials, divided equally in 6 practice sessions. During this phase, the KP' s were provided according to the group. In the first half of acquisition phase, the WNG received KP based on a wide bandwidth. In the last half of acquisition phase, this group received KP based on a narrow bandwidth. The NWG, in the first half of the acquisition phase, received KP based on a narrow bandwidth. In the last half of acquisition phase, this group received KP based on a wide bandwidth. The control group received KP based on a 0% bandwidth, which resulted on KP after each trial. Data analyzes were run in relation to the serve movement pattern (PMG) and in relation to the score (parameters). The inferential analysis was done by two-way ANOVA with repeated measures and post hoc for pair comparison. The results showed that all groups improved both PMG and parameters learning. Moreover, the GMP measure showed improvement on intermediate (p = 0.01), which was mantained on retention (p = 0.05). The parameters showed improvement only on retention test (p = 0.01). There were no statistical differences between groups (p > 0.05). These results led us to conclude that, appears to be an hierarchy of which aspect of the task was learned when the extrinsic feedback is related to PMG, identified on the initial learning of PMG and further learning of parameters